UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN PENERAPAN PENDEKATAN PROBLEM SOLVING PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM KELAS XII.IPA.2 SMA NEGERI 1 LUBUK BASUNG (Jurnal Pelangi : Research of Education and Development, 2015)
This study aims to address learning problems in SMA 1 Lubuk Basung, in particular to improve the learning outcomes of students in Pendidikan Agama Islam (PAI) in the class XII.IPA.2 SMA Negeri 1 Lubuk Basung through the use of Problem Solving Approach. The results showed the use of Problem Solving Approach successfully improve student learning outcomes, which in the first cycle in which the average value obtained new students reached 7.1 with classical completeness 71% and in the second cycle increased reach an average value of 8.31 with classical completeness of 93%. It can be concluded that the use of Problem Solving Approach to learning Pendidikan Agama Islam (PAI) succeeded in improving student learning outcomes in the class XII.IPA.2 SMA Negeri 1 Lubuk Basung